Participatory rural appraisal (PRA): An analysis of experience in Darmareja Village, Sukabumi District, West Java, Indonesia. - Mohd Yusof Hj Abdullah,; Noor Rahamah Hj Abu Bakar,; Junaenah Sulehan,; Abd. Hair Awang,; Ong Puay Liu, (Universiti Kebangsaan Malaysia, 2012)
Participatory Rural Appraisal (PRA) is an approach which encourage the community to share their opinions, ideas and experiences pertaining to the local problems, issues and needs. This approach emphasizes on local knowledge and help local community to make their own plans, analysis and appraisal. Thus, PRA is used to facilitate information sharing, analysis and action among stakeholders. The purpose of PRA is to enable the main stakeholders i.e. government, local communities, private sectors or NGOs to work together to plan appropriate and relevant programs for the community. In Indonesia, the Center for Social Empowerment, National University of Indonesia (UNAS) had been championing the use of PRA for development process. This article discusses on the use of PRA in a selected village in West Java, Indonesia. It will highlight the advantages and disadvantages of using this technique.